Cenozoic morphotectonic evolution of the eastern edge of Paraná Sedimentary Basin, southern Brazil - Sanches, Emerson; Salamuni, Eduardo; Lima da Silva, Clauzionor; dos Santos, Marcilene [UNESP]; Miranda dos Santos, Jéssica; Rudolf Lopes Peyerl, William (Elsevier, 2024)
The Paraná Sedimentary Basin (PSB) is one of the most important geotectonic structures on the South American continent and its tectono-sedimentary evolution has been widely investigated, especially during the Paleozoic and Mesozoic. However, the post-rift Cenozoic dynamics need further studies to fully understand its evolution. Hence, this research aims to add data and interpretations regarding the morphostructural features inherent in the Cenozoic tectonic framework, especially in the south/southeast region of Brazil. Here, we explore the Cenozoic processes of tectonic reactivation of preexisting structural features, as well as the neoformation of structural features, considering that Mesozoic sedimentary and volcanic strata of the Serra Geral Group in the Paraná Basin were deformed by Cenozoic joints and faults. For this purpose, structural and geomorphological (morphometric) analyses were used in the Itararé and Cinzas rivers catchments, on the eastern edge of the PSB. The study area is part of the Ponta Grossa Arch domain, in the northeast of Paraná state and southwest of São Paulo state. The structural data collected, when associated with the morphometric analyses (qualitative and quantitative), were compatible, showing the influence of tectonic structuring on the geomorphological framework of the investigated watersheds, resulting in the morphotectonic compartmentalization of the surveyed area. Alterations to the topographic surface, asymmetry patterns in the watersheds, disturbances in the longitudinal river profiles and anomalies in the drainage network patterns are the result of reactivation of ancient NE-SW and NW-SE faults in the crystalline basement and present in the units that fill the sedimentary basin, as well as new families of faults, mainly in N–S and E-W direction. The structural analysis supported the determination of the Cenozoic paleostress fields, defined from the analysis of the fault population, spatial arrangement and through statistical and mechanical treatment of the kinematic structural data. The results of the paleostress tensors indicate a landscape evolution associated with at least four tectonic pulses, which compressive SHmax values are oriented in NE-SW, N–S, NW-SE and E-W directions, respectively. These are in agreement with the main regional scientific studies in southern and southeastern Brazil, which involve tectonic events from the Upper Cretaceous and Paleogene, advancing into the Neogene and up to at least the Pleistocene.
Keywords: Cenozoic tectonics; Fault reactivation; Morphotectonics; Paleostress